Screening of α‑Glucosidase Inhibitors in Cichorium glandulosum Boiss. et Huet Extracts and Study of Interaction Mechanisms - Abudurexiti, Adalaiti; Abdurahman, Abliz; Zhang, Rui; Zhong, Yewei; Lei, Yi; Qi, Shuwen; Hou, Wenhui; Ma, Xiaoli (ACS omega, 2024)
Cichorium glandulosum Boiss. et Huet (CGB) extract has an α-glucosidase inhibitory effect (IC50 = 59.34 ± 0.07 μg/mL, positive control drug acarbose IC50 = 126.1 ± 0.02 μg/mL), but the precise enzyme inhibitors implicated in this process are not known. The screening of α-glucosidase inhibitors in CGB extracts was conducted by bioaffinity ultrafiltration, and six potential inhibitors (quercetin, lactucin, 3-O-methylquercetin, hyperoside, lactucopicrin, and isochlorogenic acid B) were screened as the precise inhibitors. The binding rate calculations and evaluation of enzyme inhibitory effects showed that lactucin and lactucopicrin exhibited the greatest inhibitory activities. Next, the inhibiting effects of the active components of CGB, lactucin and lactucopicrin, on α-glucosidase and their mechanisms were investigated through α-glucosidase activity assay, enzyme kinetics, multispectral analysis, and molecular docking simulation. The findings demonstrated that lactucin (IC50 = 52.76 ± 0.21 μM) and lactucopicrin (IC50 = 17.71 ± 0.64 μM) exhibited more inhibitory effects on α-glucosidase in comparison to acarbose (positive drug, IC50 = 195.2 ± 0.30 μM). Enzyme kinetic research revealed that lactucin inhibits α-glucosidase through a noncompetitive inhibition mechanism, while lactucopicrin inhibits it through a competitive inhibition mechanism. The fluorescence results suggested that lactucin and lactucopicrin effectively reduce the fluorescence of α-glucosidase by creating lactucin-α-glucosidase and lactucopicrin-α-glucosidase complexes through static quenching. Furthermore, the circular dichroism (CD) and Fourier transform infrared spectroscopy (FT-IR) analyses revealed that the interaction between lactucin or lactucopicrin and α-glucosidase resulted in a modification of the α-glucosidase’s conformation. The findings from molecular docking and molecular dynamics simulations offer further confirmation that lactucopicrin has a robust binding affinity for certain residues located within the active cavity of α-glucosidase. Furthermore, it has a greater affinity for α-glucosidase compared to lactucin. The results validate the suppressive impact of lactucin and lactucopicrin on α-glucosidase and elucidate their underlying processes. Additionally, they serve as a foundation for the structural alteration of sesquiterpene derived from CGB, with the intention of using it for the management of diabetic mellitus.